2018
DOI: 10.3310/hta22450
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia to reduce intracranial pressure after traumatic brain injury: the Eurotherm3235 RCT

Abstract: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in ; Vol. 22, No. 45. See the NIHR Journals Library website for further project information. The European Society of Intensive Care Medicine supported the pilot phase of this trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 139 publications
1
26
0
Order By: Relevance
“…This study showed that therapeutic moderate hypothermia (32-35 °C) plus standard care to reduce ICP led to slightly increased mortality rates and unfavourable functional outcomes compared to those with standard care alone. Furthermore, an adverse association between hypothermia and worsening multiple organ failure was noted [39,40]. A Cochrane Review (March 2016) on mild hypothermia in severe brain injury, which included 37 studies with 3110 participants, demonstrated no high-quality evidence that hypothermia reduces mortality and morbidity in patients with severe TBI [41].…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…This study showed that therapeutic moderate hypothermia (32-35 °C) plus standard care to reduce ICP led to slightly increased mortality rates and unfavourable functional outcomes compared to those with standard care alone. Furthermore, an adverse association between hypothermia and worsening multiple organ failure was noted [39,40]. A Cochrane Review (March 2016) on mild hypothermia in severe brain injury, which included 37 studies with 3110 participants, demonstrated no high-quality evidence that hypothermia reduces mortality and morbidity in patients with severe TBI [41].…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…Particularly in China where three of the four trials had positive effects (acute reduction in ICP and long-term improvement of neurological deficits and mortality at 6 months), however all other trials failed to show similar results (186) e.g., Eurotherm3235 Trial, POLAR RCT failed to reproduce the benefits and stopped due to adverse effects. In the Eurotherm trial, titration with therapeutic hypothermia successfully reduced ICP in participants with TBI + ICP of >20 mmHg, but also led to a higher mortality rate and worse functional outcome (218). Post-hoc subgroup analysis of the NABIS-HII trial revealed that hypothermia improved outcomes in patients with evacuated subdural hematomas (219).…”
Section: Vulnerable Tbi Events That Can and Need To Be Targeted By CLmentioning
confidence: 99%
“…Randomized controlled trials (RCTs), of short duration (48–72 h) mild hypothermia treatment have failed to show benefit: NABIS: H I [5] and NABIS: H II [6] did not show improvement in outcomes and reported major complications of low blood pressure or rebound intracranial pressure (ICP) increase during early rewarming [ 7 , 8 ]. The Eurotherm3235 trial in Europe more recently showed that hypothermia sustained for 48 h successfully reduced ICP but led to a higher mortality rate and worse functional outcome [9] . Two other randomized trials of mild hypothermia, the POLAR trial [10] and B-HYPO study, [11] in which hypothermia was sustained for 72 h, indicated that hypothermia did not improve neurologic outcomes at 6 months compared with normothermia.…”
Section: Introductionmentioning
confidence: 99%